2008
DOI: 10.1103/physreve.78.061113
|View full text |Cite
|
Sign up to set email alerts
|

Counterintuitive ground states in soft-core models

Abstract: It is well known that statistical mechanics systems exhibit subtle behavior in high dimensions. In this paper, we show that certain natural soft-core models, such as the Gaussian core model, have unexpectedly complex ground states even in relatively low dimensions. Specifically, we disprove a conjecture of Torquato and Stillinger, who predicted that dilute ground states of the Gaussian core model in dimensions 2 through 8 would be Bravais lattices. We show that in dimensions 5 and 7, there are in fact lower-en… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 24 publications
(50 reference statements)
1
29
0
Order By: Relevance
“…This theorem is, so far as we know, the only general-framework analogue of the special case considerations done in [17]. A similar classification in dimension 3 seems to be an interesting future direction of research.…”
Section: Asymptotic Resultsmentioning
confidence: 63%
See 2 more Smart Citations
“…This theorem is, so far as we know, the only general-framework analogue of the special case considerations done in [17]. A similar classification in dimension 3 seems to be an interesting future direction of research.…”
Section: Asymptotic Resultsmentioning
confidence: 63%
“…In this section we consider our Theorem 1.1 within the theory of fibered packings, as introduced by Conway and Sloane [19] and extended by Cohn and Kumar [17]. The basic definition is the following: Definition 2.9 (fibering configurations, cf.…”
Section: Link To the Theory Of Fibered Packingsmentioning
confidence: 99%
See 1 more Smart Citation
“…This would also shed some light on the issue of the number of operations required to construct a dense packing, which appears still quite prohibitive as d increases. For some related works in this direction on soft-core models, see [79,80].…”
Section: Perspectivesmentioning
confidence: 99%
“…Accordingly, a powerful and elegant proof on the ground-state structures of certain classes of bounded pair interactions has been established in the work of Sütő [16][17][18]. Further, Torquato and Stillinger have recently derived generalized duality relations, which act as guides in the search for ground states [19], and they also analyzed the phase behavior of the Gaussian model in high spatial dimensions [20], for which Cohn and Kumar subsequently showed that its ground states are non-Bravais lattices at spatial dimension 5 and 7 [21]. For diverging potentials, Theil has given a rigorous proof of the crystallization of LennardJones particles in two dimensions in a triangular lattice [22].…”
Section: Introductionmentioning
confidence: 99%